Diet Type Impacts Production Performance of Fattening Lambs by Manipulating the Ruminal Microbiota and Metabolome - Li, Siqi; Du, Meiyu; Zhang, Chongyu; Wang, Yun; Lee, Yunkyoung; Zhang, Guiguo (Frontiers in Microbiology, 2022)
Pelleted total mixed ratio (PTMR) performed the positive effect on productivity of fatting lambs. However, whether the benefitable effects are underpinned by altering the rumen microbiota and metabolome remain unclear. The study aimed to investigate the correlations of on the growth performance, ruminal microbiome and metabolome of lambs fed PTMR diet. A total of 100 crossbred (Dorper sheep × Fine-wool Sheep) ram lambs at 55 d of age with similar body weight (BW, 13.2 ± 0.5 kg) were randomly allocated to 10 pens that were fed either PTMR or un-pelleted total mixed ration (UPTMR) with the same dietary ingredients and nutritional contents. The average daily gain (ADG) and average daily feed intake (ADFI) were determined during the 62-day experimental period, and ruminal pH, volatile fatty acid (VFA) concentrations, microbiome, and metabolome in the rumen of the lambs were measured at the end of the experiment. Compared to UPTMR group, lambs fed PTMR had the greater ADFI (P=0.002), ADG (P=0.003), and feed efficiency (P<0.05). Similarly, feeding PTMR increased the concentration of total volatile fatty acids (TVFA) and the molar proportion of propionate, but decreased the proportion of butyrate and acetate to propionate ratio in the rumen of lambs than that of lambs fed UPTMR (P<0.05). Additionally, feeding PTMR to lambs lowered the alpha-diversity of the ruminal microbiota, whereas enhanced the relative abundance of Fibrobacter (P<0.05), Veillonellaceae (P<0.05), and tended to enhance (P=0.064) the richness of Rikenellaceae in the rumen relative to those of UPTMR group. Compared to UPTMR group, feeding PTMR to lambs significantly upregulated the metabolic pathways involving tryptophan, histidine, cysteine and methionine, beta-Alanine, tyrosine metabolisms, and steroid biosynthesis. Moreover, the abundance of the microbiota exerted a tight correlation to the alterations of performance, ruminal VFA, and metabolism pathways of lambs. Taken together, feeding PTMR characterized the ruminal microbiome of lambs with decreased diversity while improved richness of some specific microbes and upregulated certain growth-related metabolic pathways, which contributed to the augmented growth performance and feed efficiency of fattening lambs. Thus, it is a recommendable dietary strategy to feed PTMR to fattening lambs for superior production performance and feed efficiency.